Design of experiments analysis of a gas-delayed blowback system of operation - Goździk, Dawid; Morawski, Mateusz; Woźniak, Ryszard; Zahor, Mirosław; Trębiński, Radosław (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The paper presents results of an investigation into a gas-delayed blowback operation firearm system. A recently developed experimental stand was used to this end. In this article, the results are subjected to statistical analysis using design of experiments methods, including response surface methodology (RSM). This analysis facilitates the determination of the significance and nature of parameters such as distance of the gas port from the breech end of the barrel, diameter of the gas port, mass of the recoiling assembly, diameter of the gas piston rod and length of the gas chamber that influence the operation of such systems. The results of the research can be used to validate a mathematical model of a weapon operating on this principle and serve as the starting point for the optimization process of this type of design.